Phalaropus lobatus - Bishop, K. David (Zenodo, 2023)
RED-NECKED PHALAROPE Phalaropus lobatus Status Palearctic migrant. Common Palearctic migrant to waters off northern New Guinea (Beehler & Pratt 2016) including around Biak and Supiori where it is regularly seen, sometimes in large numbers, including big rafts off the north coast such as that observed in March 1930 (Mayr & Meyer de Schauensee 1939). Published as part of Bishop, K. David, 2023, The avifauna of Biak Island, Papua, Indonesia with comments on status, conservation, natural history and taxonomy, pp. 3-62 in Bulletin of the British Ornithologists' Club 143 (1) on page 34, DOI:10.25226/bboc.v143i1.2023.a2, http://zenodo.org/record/11642130